Let $c$ be a new constant symbol in the language. Then $[\forall x \neg \alpha \rightarrow \neg \alpha^{x}_{c}] \longrightarrow [\alpha^{x}_{c} \rightarrow \exists x \alpha]$ is a tautology.

This means the expression is always $\textbf{true}$ regardless of the truth assignment of all the prime formulas, which assume the form of $\forall y \beta,$ occuring in it.

Every wff in the expression is built from formulas of the form: $\forall z \beta,$ via the operations $\rightarrow$ and $\neg.$ So how do I build $\neg\alpha^{x}_{c}$ from $\forall y \beta \ ?$ And how do I assign a truth value on it?

Kindly advise. Thank you.


The formula :

$(∀x¬α → ¬α^x_c) \rightarrow (α^x_c → ∃xα)$

is a valid formula of first-order logic.

Usually, the use of tautology is restricted to propositional logic.

But we have also another prossibility : we can say that a formula of f-o logic is an instance of a tautology, in which case it is obviously valid.

To show this, we must assume that $\exists$ is an abbreviation for : $\lnot \forall \lnot$.

Start then from the tautology :

$(\varphi \rightarrow \lnot \psi) \rightarrow (\psi \rightarrow \lnot \varphi)$

and instantiate it with $∀x \lnot \alpha$ in place of $\varphi$ and $\alpha^x_c$ in place of $\psi$.

We have :

$(∀x¬α → ¬α^x_c) \rightarrow (α^x_c → ¬∀x¬α)$.

With the above abbreviation, we conclude with :

$(∀x¬α → ¬α^x_c) \rightarrow (α^x_c → ∃xα)$.

Thus, we have proved that the formula is valid, exactly because it is an instance of a tautology.


If you want to use a "semantical" argument, based on truth assignment, again you have to start form :

$(∀x¬α → ¬α^x_c) \rightarrow (α^x_c → ¬∀x¬α)$.

Assume an assignment $v$ such that $v(\alpha^x_c)=F$; then the consequent of the "main" conditional is true and the formula evaluates to true.

Assume now an assignment $v$ such that $v(\alpha^x_c)=T$.

We have two possibilities :

  • if $v(∀x¬α)=F$, then $v(¬∀x¬α)=v(∃xα)=T$, and the consequent of the conditional is true; then, the formula is true.

  • if $v(∀x¬α)=T$, then $v(¬∀x¬α)=v(∃xα)=F$, and the consequent of the conditional is false; but then, $v(\alpha^x_c)=T$ means that $v(¬\alpha^x_c)=F$, which implies that also the antecedent of the conditional is false. Thus, the formula is again evaluated to true.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.